A techno-economical assessment of solar/wind resources and hydrogen production: A case study with GIS maps. (15th May 2019) - Nematollahi, Omid; Alamdari, Pouria; Jahangiri, Mehdi; Sedaghat, Ahmad; Alemrajabi, Ali Akbar
Abstract: Providing electricity generation is a crucial indicator for development of a country's progress index. Renewable energy resources are rapidly being recognized as important alternatives for clean production of electricity. The present paper aimed to assess the wind and solar data from selected metrological stations in the province of Sistan and Baluchistan in Iran in order to produce hydrogen as a clean fuel. For using wind and solar energies, a detailed techno-economical analysis was presented. At first, the solar energy potential was assessed; indicating that the most part within the province possesses a high radiation intensity of more than 500 W/m 2 . Secondly, wind resources were examined, revealing the high power density of about 500 W/m 2 in Lutak station. According to evaluation of hydrogen production from several small wind turbines, it was shown that the maximum amount of 39.7 ton-H2 can be produced every year. It was observed that in the best conditions, the cost of 1 kWh electrical energy generated by wind turbine was 2 cents cheaper than the market energy unit price while this value is 8 cents cheaper by employing both wind and solar energies. GIS maps of hydrogen production, wind speed, wind power and global horizontal radiation were produced. Highlights: Wind/solar potentials in the province of Sistan & Baluchistan in Iran are assessed. A detailed techno-economical analysis is presented using wind/solar energies. Economical solar energy above 500 W/m 2 is observed in several stations. High hydrogen production of 39.7 ton-H2 is observed in Lutak station. The GIS maps of solar/wind/hydrogen are reported.